Analyzing the Determinants of the Gender Development Index (GDI) with an Ordinal Logistic Regression Approach - Izza, Ananda Nur; Farida, Yuniar (Universitas Islam Indonesia, 2026)
Regional disparities in the gender development index (GDI) across districts and cities in East Java reflect unequal gender development outcomes despite provincial progress. These disparities are associated with differences in access to health, education, and economic opportunities. This study identified the determinants of GDI using a gender-specific ordinal logistic regression model based on district/city-level data. The analysis included indicators representing health, education, and economic dimensions. Results showed that the determinants of GDI differed by gender. For males, life expectancy and expected years of schooling significantly increased the likelihood of a region being classified into a higher GDI category. For females, expected years of schooling and mean years of schooling were the most influential factors, emphasizing the importance of educational access and attainment. The model demonstrated moderate explanatory power for male data (Nagelkerke R-squared = 0.414) and strong explanatory power for female data (Nagelkerke R-squared = 0.654). However, the models exhibited relatively high classification error rates, with misclassification rates of 39.47% for males and 52.63% for females. These findings provide evidence that the drivers of gender development vary by gender and offer practical insights for designing targeted, gender-responsive policies to reduce regional disparities and promote inclusive development in East Java.